Development of constructed wetlands in performance intensifications for wastewater treatment: a nitrogen and organic matter targeted review - Wu, Shubiao; Kuschk, Peter; Brix, Hans; Vymazal, Jan; Dong, Renjie (Water research, 2014)
The knowledge on the performance enhancement of nitrogen and organic matter in the expanded constructed wetlands (CWs) with various new designs, configurations, and technology combinations are still not sufficiently summarized. A comprehensive review is accordingly necessary for better understanding of this state-of-the-art-technology for optimum design and new ideas. Considering that the prevailing redox conditions in CWs have a strong effect on removal mechanisms and highly depend on wetland designs and operations, this paper reviews different operation strategies (recirculation, aeration, tidal operation, flow direction reciprocation, and earthworm integration), innovative designs, and configurations (circular-flow corridor wetlands, towery hybrid CWs, baffled subsurface CWs) for the intensifications of the performance. Some new combinations of CWs with technologies in other field for wastewater treatment, such as microbial fuel cell, are also discussed. To improve biofilm development, the selection and utilization of some specific substrates are summarized. Finally, we review the advances in electron donor supply to enhance low C/N wastewater treatment and in thermal insulation against low temperature to maintain CWs running in the cold areas. This paper aims to provide and inspire some new ideas in the development of intensified CWs mainly for the removal of nitrogen and organic matter. The stability and sustainability of these technologies should be further qualified.
Keywords: dusík; odpad tekutý - odstraňování; Waste Disposal, Fluid; Organic Chemicals; Operation strategy; Wastewater treatment; odpadní voda; Waste Water; Constructed wetlands; Wetlands; organické látky; mokřady; Performance enhancement; Wastewater; Nitrogen